2010
DOI: 10.1111/j.1467-839x.2010.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Saving graces: Impact of partner support and maternal attachment on partner attachments in an individualistic and a collectivist context

Abstract: The current study investigated the relationships between current attachment to mother and attachment to romantic partners, and the role of current partner support and culture as moderators of that relationship. University students who were currently in a romantic relationship were recruited from Hong Kong and USA, and completed measures on attachment styles and partner support. Results showed that maternal attachment anxiety was correlated with romantic attachment anxiety; maternal attachment avoidance was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…However, as we have not measured relatedness in the present study, this possible explanation would need further investigation to substantiate the claim. The results are consistent with the findings of Ho et al. (2010) and Chen et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, as we have not measured relatedness in the present study, this possible explanation would need further investigation to substantiate the claim. The results are consistent with the findings of Ho et al. (2010) and Chen et al.…”
Section: Discussionsupporting
confidence: 92%
“…The findings relevant to the association between predictors of romantic relationship styles or the association between romantic relationship styles or coping styles and well‐being were also inconclusive. Ho et al. (2010) found that the linkage between partner support and romantic attachment avoidance was stronger among Hong Kong Chinese than among Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the common avoidance features of PTSD did not extend to all attachment figures in a consistent fashion. Initial conceptualizations of attachment theory posited that an overarching internal working model would be relatively stable across different figures (Bretherton and Munholland 1999;Weiss 1994), and some studies have reported correlations between childhood attachments and adult attachment styles (e.g., Ho et al 2010). However, the differential attachment results in this exploratory study are consistent with a growing body of research demonstrating that attachments to different figures have been found to be independent (Bernier and Matte-Gagné 2011;Lindberg et al 2015b;Lindberg et al 2015a;Lindberg et al 2012;Lindberg and Thomas 2011;Madigan et al 2011).…”
Section: Discussionsupporting
confidence: 75%
“…Particularly, Chinese culture is extremely social‐oriented and stresses context communication (Hofstede, ). Chinese are strongly affected by normative and social values (Ho et al ., ).…”
Section: Introductionmentioning
confidence: 97%